Protein Phosphatase 2A Regulates Cardiac Na+ Channels. Issue 5 (1st March 2019) - El Refaey, Mona; Musa, Hassan; Murphy, Nathaniel P.; Lubbers, Ellen R.; Skaf, Michel; Han, Mei; Cavus, Omer; Koenig, Sara N.; Wallace, Michael J.; Gratz, Daniel; Bradley, Elisa; Alsina, Katherina M.; et al.
Abstract : Rationale: : Voltage-gated Na + channel ( I Na ) function is critical for normal cardiac excitability. However, the Na + channel late component ( I Na, L ) is directly associated with potentially fatal forms of congenital and acquired human arrhythmia. CaMKII (Ca 2+ /calmodulin-dependent kinase II) enhances I Na, L in response to increased adrenergic tone. However, the pathways that negatively regulate the CaMKII/Nav 1.5 axis are unknown and essential for the design of new therapies to regulate the pathogenic I Na, L . Objective: : To define phosphatase pathways that regulate I Na, L in vivo. Methods and Results: : A mouse model lacking a key regulatory subunit (B56α) of the PP (protein phosphatase) 2A holoenzyme displayed aberrant action potentials after adrenergic stimulation. Unbiased computational modeling of B56α KO (knockout) mouse myocyte action potentials revealed an unexpected role of PP2A in I Na, L regulation that was confirmed by direct I Na, L recordings from B56α KO myocytes. Further, B56α KO myocytes display decreased sensitivity to isoproterenol-induced induction of arrhythmogenic I Na, L, and reduced CaMKII-dependent phosphorylation of Nav 1.5. At the molecular level, PP2A/B56α complex was found to localize and coimmunoprecipitate with the primary cardiac Nav channel, Nav 1.5. Conclusions: : PP2A regulates Nav 1.5 activity in mouse cardiomyocytes. This regulation is critical for pathogenic Nav 1.5 late current and requires PP2A-B56α. Our study supports B56α as a novel target for the treatment of arrhythmia. Abstract : Supplemental Digital Content is available in the text.